Development of an in vitro model of functional mitral valve regurgitation - Pouching, Kristal, author; Monnet, Eric, advisor; Orton, Christopher, committee member; James, Susan, committee member (Colorado State University. Libraries, 2012)
Functional or ischemic mitral regurgitation (FMR) is a common sequelae to various cardiomyopathies which result in altered cardiac geometry secondary to ventricular remodeling. The causative architectural changes are typified by apical tethering of the mitral valve leaflets by ventricular dilation and papillary muscle repositioning, and is usually accompanied by annular dilation and mitral valve leaflet malcoaptation. The resultant mitral regurgitation (MR) and consequent volume overload contributes to further ventricular remodeling and perpetuation of the clinical scenario. The present mainstay of surgical therapy involves annular undersizing with the use of annuloplasty rings. However, surgical interventions thus far have been limited by numerous shortcomings and inconsistent results emphasizing the need for continued research into the mechanics of FMR correction. In this study a novel invitro model of FMR utilizing explanted ovine hearts was introduced as a tool for investigating the mechanism of FMR and determining strategies aimed at correction. In the first phase of model development FMR was induced by either annular dilation or papillary muscle repositioning in a static flow system. Both techniques were individually able to significantly increase the regurgitant volume from baseline (annular dilation: baseline 15.5ml/10s to 78.7 ± 35.3 ml/10s, p =0.02, patch: baseline 7.6ml/10s to 67.4 ± 30.4 ml/10s, p =0.02) with no significant differences between the two groups and a marked increase in regurgitant volume noted when both techniques were applied together (p =0.0001). The devised technique of papillary muscle displacement by patch placement successfully recreated the outward rotation and increased LV sphericity (baseline: 3.25±0.7, patch: 2.34±0.6, p =0.0025) observed clinically. For the second phase of the study the developed model was investigated in a pulsatile flow system with FMR induced by posterior papillary muscle displacement only. A timed, positive pressure valve pump with a set rate of 80 simulated beats/min and approximate flow rate of 6L/min was used and procured results even more pronounced than that recorded for the static flow system (static flow system MR vol: 67.4±30.4ml/10s vs. pulsatile flow system MR vol: 310.5 ± 86.6ml/10s). The final investigation involved subjection of the developed FMR model to geometric modifications aimed at correcting MR in the pulsatile flow system. Attempts were made to correct the modeled papillary muscle displacement until the regurgitant volume was eliminated/minimized and the associated LV dimensions measured. The results showed that correction of the apical tethering of the chordae was sufficient to significantly reduce MR volume (patch: 310±86.6ml/10s vs. displacement correction: 16.1 ± 23.7ml/10s, p =0.0001) despite failure to return to baseline dimensions. In the developed model, which has been demonstrated to be amenable to both pulsatile and static flow systems, annular dilation and posterior papillary repositioning were both able to individually induce FMR and significant increases in regurgitant volume was noted once the two techniques were combined. The role of posterior papillary muscle repositioning in the correction of this disease was emphasized. The developed model provided evidence for the possibility of FMR elimination by geometric alterations beyond restoration of baseline/pre-disease dimensions with direct clinical implications to the surgical treatment of affected patients.
Keywords: functional mitral valve regurgitation; mitral valve insufficiency; mitral valve; ischemic mitral valve regurgitation; in vitro model